Comparison of Natural Materials for Colour Removal from Textile Effluent - Patel, Himanshu; Vashi, R.T. (Asian Journal of Chemistry, 2010)
The comparative studies of three natural materials i.e. bentolite, zeolite and fuller's earth for colour removal from textile waste water has been investigated, in which zeolite is found to be most effective among these natural materials. Various parameters like adsorbent dosage, temperature, contact duration and agitator speed have been considered in this studies. The Freundlich and Langmuir isotherm are used to analyze the data. The total decolourization was found at zeolite dosage of 50 g/L at tempe-rature of 310 K and contact duration of 4 h.